Silver nanocubes monolayers as a SERS substrate for quantitative analysis - Zhou, Ziang; Bai, Xiuhui; Li, Peishen; Wang, Changzheng; Guo, Ming; Zhang, Yang; Ding, Peiren; Chen, Shaowei; Wu, Yunyun; Wang, Qiang (Chinese chemical letters, 2021)
With adding 1-dodecanethiol-ethanol mixture, the Ag nanocubes was deposited as edge-to-edge monolayer onto the PE/gold film surface, leading to improved SERS efficiency. [Display omitted] Surface-enhanced Raman scattering (SERS) is a powerful spectroscopic tool in quantitative analysis of molecules, where the substrate plays a critical role in determining the detection performance. Herein, a silver nanocubes/polyelectrolyte/gold film sandwich structure was prepared as a reproducible, high-performance SERS substrate by the water/oil interfacial assembly method. In addition to the hot spots on the nanocubes surface, the edge-to-edge interspace of the Ag nanocubes led to marked enhancement of the SERS intensity, with a limit of detection of 10−11 mol/L and limit of quantitation of 10−10 mol/L for crystal violet. When rhodamine 6G and crystal violet were co-adsorbed on the Ag nanocube surfaces, the characteristic SERS peaks of the two molecules remained well resolved and separated, and the peak intensities varied with the respective concentration, which could be exploited for concurrent detection of dual molecules. Results from this work indicate that organized ensembles of Ag nanocubes can serve as effective SERS substrate can for sensitive analysis for complex molecular systems.